PROBLEM-BASED LEARNING USHUL FIQH IN THE ESTABLISHMENT OF STUDENT MODERATION ATTITUDE IN MADRASAH - Sapiudin Sapiudin; Zainuddin Zainuddin; Muhammad Muhtarom Salman (Penamas, 2022)
The study of Usul Fiqh, in general, is still conventional-doctrinal. On the other hand, there are still attitudes of madrasa students that are indicated to be intolerant. This study aims to analyze the moderation attitude of students from the application of problem-based learning of Ushul Fiqh. This research uses a qualitative approach with a field research model through observation, interviews, and documentation. The results showed that the problem-based learning model of Ushul Fiqh from the material aspect was based on Arabic books (Kitab Kuning); the method used consisted of tatbiiq, musykilat, and bahtsul masail. The evaluation used measured attitudes and skills. The application of Ushul Fiqh learning has been able to build student moderation attitudes based on tolerance (tasamuh), consultation (syuro), and exemplary (al-qudwah). This finding can be an alternative model for building student moderation attitudes.